2020
DOI: 10.2478/kbo-2020-0102
|View full text |Cite
|
Sign up to set email alerts
|

Particularities of the Military Leadership in the Context of Social Networking

Abstract: The evolutions in the theaters of operations have highlighted in the last decades a profound change of the realities in the sense of the increasingly obvious contouring of an enemy whose characteristics are specific to the social networking. Since the classic ways of action are inefficient under these circumstances, it became necessary to investigate and explain the new realities. In this context, military leadership acquires certain particularities that concern, on the one hand its essential foundations and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…For instance,Hassan et al (2018) found that the networking ability of leaders does not happen alone but is dependent upon other factors like external monitoring and representation for them to become influential leaders. In another study,Sfârlog et al (2020) pointed out that leadership is relational and interactive, even in the military, moving towards a network perspective, capitalizing on network relationships. This kind of relationship results in a seamless collaboration with other organizations, positively impacting the organizations.…”
mentioning
confidence: 99%
“…For instance,Hassan et al (2018) found that the networking ability of leaders does not happen alone but is dependent upon other factors like external monitoring and representation for them to become influential leaders. In another study,Sfârlog et al (2020) pointed out that leadership is relational and interactive, even in the military, moving towards a network perspective, capitalizing on network relationships. This kind of relationship results in a seamless collaboration with other organizations, positively impacting the organizations.…”
mentioning
confidence: 99%